Implementasi 5S Sebagai Upaya Peningkatan Efisiensi pada Produksi Cetakan Roster di UD ABXYZ - Burhanuddin, Ilham Fatoni; Hamidah, Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Increasing production efficiency is an important factor in maintaining company competitiveness, especially in the small and medium industry sector. One approach that can be applied to achieve this efficiency is the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke), which focuses on establishing an orderly, clean, and disciplined work culture. This study aims to analyze the application of the 5S method as an effort to increase the efficiency of the roster mold production process at UD Abxyz. This activity was carried out in the form of Field Work Practice (PKL) as an implementation of industrial theory into the real world of work. The methods used included direct observation, interviews, analysis of 5S implementation, and evaluation before and after the implementation of improvements. Data were collected using a checklist audit sheet and analyzed descriptively to measure changes in work efficiency and regularity. The results showed that the implementation of the 5S method was able to increase work efficiency and productivity. The 5S condition assessment score increased from 22.22% (poor category) to 60% (sufficient category) after implementation.